Explorando vulnerabilidades em projetos com FPGAs por meio da inserção de trojans de hardware - Lima, Iago Oliveira (2019)
Security in the digital environment has always been a very worrying area, especially with the overwhelming growth of new technologies. In the last decades, research in the field of hardware security has grown as a number of security vulnerabilities and hardware attacks have been discovered around the world, for example, the 2012 US Senate Armed Forces report exposed several counterfeit devices in various branches of the Air Forces. Reports of hardware trojans have been growing exponentially, identifying this type of trojan is a time-consuming task. This paper explores different fictional scenarios involving the insertion of hardware trojans. In order to demonstrate the process of hardware attack.